Transformation of democratic values in lakon Petruk Dadi Ratu: A cultural and political perspective - Andriansyah, Tommy; Umam, Khaerul; Muhammad, Hafizh Yusuf; Al Hamid, Islam; Wahidah, Andiena Asnal; Ayunin, Prudence Queisha Qurrota; Nafisah, Aqila Zakiya (MID Publisher International, 2025)
This study aimed to analyze the transformation of democratic values reflected in the play Petruk Dadi Ratu from a cultural and political perspective. The story tells the story of a minor character, Petruk, who suddenly becomes a leader, reflecting socio-political dynamics that are relevant to the context of democracy in Indonesia. The symbolism in this play has criticized the abuse of power, corruption, and leadership without competence. A qualitative approach with content analysis method was used to interpret the symbolic meaning and democratic values in the play. The results show that Petruk Dadi Ratu contains messages about the importance of integrity, justice, equality, and people's participation in the government system. In addition to being a medium of entertainment, this play has an educational function, builds social awareness, and becomes a reflection on the condition of Indonesian politics, especially related to the challenges of oligarchy and moral crisis in leadership. Thus, Petruk Dadi Ratu contributes to preserving local culture while supporting the formation of democratic awareness based on traditional values.